Teacher Training for Sustainable Agriculture: Green Fertilization in Debate - Rafael Rossi; Cassiano Garcia Roque (Universidade Federal do Norte do Tocantins, 2024)
This article is an instrument through which we discuss the importance of teacher training oriented towards quality education and sustainable agriculture, as necessary objectives for a societal process that values ​​human needs. We demonstrate the multidimensionality, procedural, ethical and scientific nature of sustainable development and explain the importance of green manure for the recovery of areas with degraded soils. Our objective is to explain green manure as a necessary study and practice in rural education. The methodology used is based on a bibliographic review and practical teaching in a degree course in rural education and agronomy. We conclude with the need to value research and teaching practices that defend sustainability, such as green manure, in all dimensions of teacher training.